Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.04.19.20071563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 experience: first Italian survey on healthcare staff members from a Mother-Child Research Hospital using combined molecular and rapid immunoassays test

Abstract: The fast spread of the novel coronavirus (SARS-CoV-2) has become a global threat hitting the worldwide fragile health care system. In Italy, there is a continued COVID-19 growth of cases and deaths that requires control measures for the correct management of the epidemiological emergency. To contribute to increasing the overall knowledge of COVID-19, systematic tests in the general population are required.Here, we describe the first Italian survey performed in 727 employees belonging to a Mother-Child Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
(13 reference statements)
4
17
0
Order By: Relevance
“…The levels of seroprevalence for CLA IgG (2.28%) at the beginning of the study and of seroconversion to this antibody (5.98%) are comparable to those reported in other studies and, overall, higher than those observed in the general population [1][2][3][4][5][6]. In a comparable study in England that followed 200 front line HCW for two weeks, they found that 20% of them seroconverted during the study, but 25% were already seropositive at the beginning of the study [1].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The levels of seroprevalence for CLA IgG (2.28%) at the beginning of the study and of seroconversion to this antibody (5.98%) are comparable to those reported in other studies and, overall, higher than those observed in the general population [1][2][3][4][5][6]. In a comparable study in England that followed 200 front line HCW for two weeks, they found that 20% of them seroconverted during the study, but 25% were already seropositive at the beginning of the study [1].…”
Section: Discussionsupporting
confidence: 82%
“…During the SARS-CoV-2 pandemic healthcare workers (HCW) have been shown to have an increased risk of infection [1][2][3][4][5][6]. Studies in this population in many parts of the world have shown seroprevalences of between 2.4% and 45%, and in general above that of the general population and varing according to multiple factors [1][2][3][4][5][6]. In asymptomatic HCW, at the peak of the pandemic in England, a global seroprevalence rate of 24.4% was found [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen articles -9 preprints, 3 published studies, and 2 government reports-from 10 countries (Brazil (2), Spain (2), United States of America (USA) (2), Germany (2), and one each from Italy, Croatia, Iran, Luxembourg, Switzerland and the Channel Islands) that tested a combined total of 100,557 participants met eligibility criteria for the estimation of the primary outcome. [14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Resultsmentioning
confidence: 99%
“…The study populations included a randomly sampled general populations 17,[20][21][22][23][24][25][26][27] ; most health care workers (HCWs) of hospitals 14,16 ; most industry workers 18,19 ; and all parturient women. 15 (Table 1) Eight studies tested adults only (>16 years) [14][15][16]18,19,23,24,27 and six tested population of all ages 17,[20][21][22]25,26 -the proportion of children and young people (0-19 years) ranged from 9% to 34% and the proportion of participants aged over 70 years ranged from 0% to 14%. Ten studies tested for both anti-SARS-CoV-2 IgG and IgM, the rest tested for IgG only or IgG and IgA.…”
Section: Figure 1 Screening and Selection Of Articles For The Reviewmentioning
confidence: 99%
“…As COVID-19 will be with us throughout 2020 and beyond, it is unrealistic for us to think about returning to pre-crisis activity in the next few months, and this condition is likely to be shared by nearly all endoscopy units in Italy. At present, polymerase chain reaction testing prior to procedures is not available in Italy; antibody testing is available but is only marginally useful as less than 20 % of average-risk people are positive [3]. The great challenge of the resume phase is thus represented by the need to redesign the organization models of endoscopy units and their interaction with territorial services.…”
mentioning
confidence: 99%